1996
DOI: 10.1021/cm9504910
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Line-Narrowing Study of Eu3+-Doped Sol−Gel Silica:  Effect of Modifying Cations on the Clustering of Eu3+

Abstract: Fluorescence line-narrowing spectroscopy is used to characterize the effect of metal cation codopants (Sr2+, La3+, Gd3+, Y3+, Lu3+, Sc3+, and Ga3+) on the state of aggregation of Eu3+ in sol−gel silica. Significant Eu3+ clustering occurs in samples doped only with Eu3+. The addition of codopants inhibits the clustering of Eu3+ and promotes better dispersion of Eu3+ in the glasses. The extent of the inhibition of clustering increases with field strength of the codopant and levels off at high field strength. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 55 publications
4
86
0
Order By: Relevance
“…The main limitation of particle analyzer is that, it only measures the hydrodynamic radius of the particle and not the actual size of the particle Costa et al (1996). Therefore, data produced can be misleading and not absolute, it should be used in conjunction to other techniques.…”
Section: Particle Analyzer Analysis Of Tm-doped Alumina Nanoparticlesmentioning
confidence: 99%
“…The main limitation of particle analyzer is that, it only measures the hydrodynamic radius of the particle and not the actual size of the particle Costa et al (1996). Therefore, data produced can be misleading and not absolute, it should be used in conjunction to other techniques.…”
Section: Particle Analyzer Analysis Of Tm-doped Alumina Nanoparticlesmentioning
confidence: 99%
“…Fibres up to 1 m length were drawn 35 . These fibres were studied for pH sensing and as laser dye when appropriately doped by fluorescent molecules, viz., fluorescein and rhodamine-6G 36,37 The special network structure can be used in sound detection 40 . Porous silica films are also used as adsorbents, scaffolds for composite material synthesis, in separation technology 42 , and molecular and biological engineering 43 .…”
Section: Sol-gel Glasses Optical Fibres and Nanocomposite Materialsmentioning
confidence: 99%
“…Fibres up to 1 m length were drawn 35 . These fibres were studied for pH sensing and as laser dye when appropriately doped by fluorescent molecules, viz., fluorescein and rhodamine-6G 36,37 . Nanoparticles of semiconductors or metals have been widely investigated for applications in nonlinear optics 38 .…”
Section: Sol-gel Glasses Optical Fibres and Nanocomposite Materialsmentioning
confidence: 99%
“…Dopant clustering is deleterious because it leads to concentration quenching of luminescence through cross-relaxation and energy transfer processes. In previous work, it was shown a method for detecting rare earth clustering in sol-gel glasses based on Eu 3+ fluorescence line narrowing spectroscopy 9 . Fluorescence line narrowing (FLN) is a site-selective spectroscopy designed to combat inhomogeneous spectral broadening in glass.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence line narrowing (FLN) is a site-selective spectroscopy designed to combat inhomogeneous spectral broadening in glass. It was reported that the addition of metal cations co-dopants leads to some inhibition of the tendency for Eu 3+ to aggregate in a gel-derived SiO 2 matrix 9 . Dopant ion encapsulation by complex-forming ligands has been achieved in order to inhibit clustering of the dopant ions 10,11 .…”
Section: Introductionmentioning
confidence: 99%